2016
DOI: 10.4103/0019-5049.181590
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomical aspects of anaesthetic practice

Abstract: Anaesthesiologist's service begins as a general physician, goes on as an investigator cum data analyser leading to the architectural planning of a forthcoming surgical event, but only after articulately convincing the subject along with his kith and kin. In the era of rapid developments in the field of medicine which includes relevant developments in anaesthetic care, an adequate work environment has to be provided to the anaesthesia team so that all anaesthetic procedures can be carried out safely and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[ 6 ] Therefore, it is crucial to consider ergonomics and adopt proper techniques to minimise the risk of long-term injury from the performer's standpoint and ensure optimal patient care. [ 7 ] The results of our study indicated no significant difference in the posture adopted by anaesthesiologists while performing laryngoscopy or intubation in either the supine or backup HELP, which we infer from the lack of notable variation in the degree of neck flexion, wrist deviation, elbow flexion and lower back flexion. Hence, anaesthesiologists should not be apprehensive of discomfort while performing laryngoscopy and intubations with patients in 25° backup HELP, especially since sufficient evidence shows that this positioning provides better glottic visualisation.…”
Section: Discussionmentioning
confidence: 65%
“…[ 6 ] Therefore, it is crucial to consider ergonomics and adopt proper techniques to minimise the risk of long-term injury from the performer's standpoint and ensure optimal patient care. [ 7 ] The results of our study indicated no significant difference in the posture adopted by anaesthesiologists while performing laryngoscopy or intubation in either the supine or backup HELP, which we infer from the lack of notable variation in the degree of neck flexion, wrist deviation, elbow flexion and lower back flexion. Hence, anaesthesiologists should not be apprehensive of discomfort while performing laryngoscopy and intubations with patients in 25° backup HELP, especially since sufficient evidence shows that this positioning provides better glottic visualisation.…”
Section: Discussionmentioning
confidence: 65%
“…The purpose of ideal ergonomics is to avoid inappropriate posture or position of the hands, wrists, neck, trunk, and shoulders, thereby causing strain to performer. [ 5 ] In this series, interscalene, supraclavicular, and infraclavicular blocks were performed by keeping the US machine on the same side of block which is against the usual ergonomics [Figure 1a and b ]. Axillary fossa block was performed in three patients along with a rescue block (radial nerve block) in one patient with standard ergonomics.…”
mentioning
confidence: 99%